In vitro studies of the digestibility of watermelon (Citrullus lanatus) peel via gas production method - Ahmad Daud, Syahira (2016)
From time to time, Malaysians are always looking for watermelon as one of their favourite fruits. The flesh is appealing to eat freshly or being blended into a refreshing drinking juice. However, the peels are left abundantly. As one of the agriculture-by-products, the excess watermelon peel are then being carried into a study to determine the digestibility of watermelon (Citrullus lanatus) peel via dry matter (DM), ash, crude protein (CP), crude fibre (CF), neutral detergent fibre (NDF), acid detergent fibre (ADF), acid detergent lignin (ADL), in vitro gas production (IV) and in vitro dry matter digestibility (IVDMD). Napier grass (Pennisetum purpureum) is used in this experiment acting as the basal diet for the ruminants. First treatment consists of (T1 = 100% Napier grass + 0% watermelon peel; n=3) followed by Treatment 2 consists (T2 = 90% Napier Grass + 10% Watermelon Peel; n=3), Treatment 3 consists of (T3 = 80% Napier grass + 20% Watermelon peel; n=3), and Treatment 4 consisting (T4 = 70% Napier grass + 30% Watermelon peel; n=3). Meanwhile, 100% of watermelon peel (n=3) act as control for this experiment. Based on the analysis, it shows that the Dry Matter (DM), ash, crude protein (CP), in vitro gas production (IV) and in vitro dry matter digestibility (IVDMD) has shown significant results (P<0.05) compared to the neutral detergent fibre (NDF), acid detergent fibre (ADF), acid detergent lignin (ADL). In IVDMD, Treatment 4 shows the best results (47.50%) indicate that it has the highest digestibility compare to other treatments. Hence, it is proved that watermelon peel is a good agriculture-by-products. In the study of in vitro gas production, watermelon peels in Treatment 4 shows good results proving that it can easily being digested by ruminants. As recommendation, the excessively abundant watermelon peels should be utilized as animal feed as one of agriculture by-product. In conclusion, as a high digestibility feed ingredient, watermelon peel should be recycled as the animal feed of small ruminants as it gives a good digestibility and highly nutritious to the animal.